A light in a sea of darkness: the moderating role of emotional complexity in the PTSD symptoms-successful aging association. (3rd June 2018) - Bodner, Ehud; Hoffman, Yaakov; Palgi, Yuval; Shrira, Amit
ABSTRACT: Objectives: This study aimed to assess the underexplored effects of posttraumatic stress disorder (PTSD) symptoms on objective and subjective successful aging and to inquire whether emotional complexity moderates these effects. Methods: Community-dwelling older adults ( N = 127, mean age = 67.86, SD = 11.07) rated their PTSD symptoms and completed measures of objective and subjective successful aging. They further reported their emotions on a daily basis over 14 days. Results: After controlling for background characteristics, self-rated health and cumulative lifetime adversity, results showed that higher PTSD symptoms were related to less successful aging, both objective and subjective. However, this relationship existed only amongst older adults with low emotional complexity, but not amongst those with high emotional complexity. Conclusion: The findings suggest that high emotional complexity buffers against the negative effects of PTSD symptoms on successful aging. Interventions that empower emotional complexity amongst traumatized older adults may attenuate these negative effects.